Cephalic Index of Korean Children With Normal Brain Development During the First 7 Years of Life Based on Computed Tomography - Heesung Nam; Nami Han; Mi Ja Eom; Minjung Kook; Jeeyoung Kim (Annals of Rehabilitation Medicine, 2021)
Objective To identify the normal range, distribution, and age-dependent differences in the cephalic index (CI) of Korean children with normal brain development and develop a classification of the current CI for Korean children up to 7 years of age. Methods We retrospectively analyzed 1,389 children who visited our hospital in the emergency room between October 2015 and September 2020 because of suspected head injuries. Finally, 1,248 children (741 male and 507 female) were enrolled after excluding abnormal medical or familial history and divided into 10 groups by age. The CI was measured using brain computed tomography and calculated according to the following equation: cephalic width/cephalic length×100. Results The averages of CI by age groups were as follows: 89.29 (0–3 months group, n=44); 91.41 (4–6 months group, n=63); 89.68 (7–9 months group, n=62); 87.52 (10–12 months group, n=41); 87.64 (≥2 years group, n=243); 86.63 (≥3 years group, n=178); 85.62 (≥4 years group, n=232); 85.77 (≥5 years group, n=201); 85.15 (≥6 years group, n=75); and 85.34 (≥7 years group, n=109). The CI of Korean children in normal brain development was confirmed to be large, showing a notable difference compared to that of Caucasians. Conclusion The current CI of Korean children will provide a valuable reference for diagnosing and treating cranial deformities, especially dolichocephaly and brachycephaly as well as to monitor the morphology of the cranium in clinics.